The economic costs of taxation: An assessment of the Henry Tax Review - Carling, R.; Pope, Jeffrey (Taxation Institute of Australia, 2011)
The Henry Review of Australia’s Future Tax System released by the Rudd Government in May 2010 is one of the most comprehensive reviews of the tax and transfer system ever undertaken. This paper considers the economic efficiency and simplicity criteria in an evaluation of the implications of the Review for the economic costs of the tax system, including the trade-offs involved. While the Review recommendations represent an improvement, they could have gone further. The Review recognises Australia’s high degree of vertical fiscal imbalance as a problem although some of its recommendations would exacerbate this imbalance. Whilst it explores the devolution of some personal income tax power to the states as a possible remedy, it unfortunately stops short of recommending this reform. Initial calculations based on the Review’s estimates of Marginal Deadweight Costs (MDCs) of selected taxes indicate that for a given overall tax/Gross Domestic Product ratio the modeled recommendations would lower the average MDC of the tax system by around 10 cents per dollar, mainly arising from the cut in the corporate income tax rate, reform of state taxes and the replacement of royalties with a Resource Rent Tax. However the modelling assumptions are open to some criticisms. Of eleven personal tax simplification reform areas identified, the Review has arguably recommended a bold measure in only five, with two rejections and the remaining four being compromise or modest proposals for reform. Over the areas of tax simplification assessed, at best the Review has been mindful of Australian tax culture and precedent and is thus politically realistic in its proposals and at worst is open to some significant criticism. Overall, apart from a minority of recommendations, the Review is moderate in its approach to tax reform from an economic efficiency and simplification perspective.